Undergraduate Students' Perception of Hybrid Learning: Voices from English Language Education Students in Pandemic Era - Setia Erliza; Puteri Anugrah Septianingsih (Journal of English Language Teaching and Linguistics, 2022)
The policy in learning has been changed by  the government since the Covid 19 cases decreased significantly in Indonesia. Therefore, the implementation of learning in this current era, especially in university level, is conducted limitedly in face to face learning mode known as Pembelajaran Tatap Muka (PTM) terbatas and online learning mode, named  Pembelajaran Jarak Jauh (PJJ). These mixed modes of learning are acclaimed as hybrid learning. This transition of learning potentially raises various perceptions among the undergraduate students. Hence, this study aims at  investigating the undergraduate students’ perception of hybrid learning system in the pandemic era. The participants of this study were 45 English department undergraduate students at State University of Malang. They were 38 females students and 7 males students from the 2nd, 6th and 8th semesters. This study was carried out through survey research design. Henceforth, the data of this study was gathered by spreading a closed-ended questionnaire via Google Form. The findings revealed that the undergraduate students showed positive perceptions regarding hybrid learning in pedagogical, social, and technical aspects. Notwithstanding, the negative perceptions were found in the technical aspects relating to students’ concentration in deeper learning and students’ difficulties in learning English during hybrid learning. Regardless of the positive and negative perceptions, according to the findings, hybrid learning can be categorized as the effective learning approach as well as the learning solution in this current pandemic era.